The use of Arduino as a safe alternative in the handling of machines in the rural environment, especially the forage shredder (International Journal of Geoscience, Engineering and Technology, 2021)
This article presents the development of a code for a device that will assist in the safe handling of the forage shredder machine. Through the use of the Arduino sensor, it is intended to limit a "risk zone", so that the worker's hand is not reached during the machining process and, if this occurs, it is proposed that a relay cut the power to the machine. This is because, over the years, the equipment previously available only to large producers became accessible also to small ones, but it was noticed that the number of incidents in the field grew dramatically due to the lack of adequate attention and training of users and, in addition to the absence of safety equipment, among others. Thanks to the research results, it was possible to prove that the government will save a lot with resources destined to pay compensation for accidents. Furthermore, the project proves to be efficient and low-cost for rural producers.
Keywords: Producers; Arduino; Incidents; Machine